The shackled continent : power, corruption, and African lives - Guest, Robert (Washington [D.C.] : Smithsonian Books, 2004)
Donated by Friends of the Library.
Introduction: Why Is Africa So Poor? -- The Vampire State -- Digging Diamonds, Digging Graves -- No Title -- Sex and Death -- The Son of a Snake is a Snake -- Fair Aid, Free Trade -- Of Potholes and Grasping Gendarmes -- Wiring the Wilderness -- Beyond the Rainbow Nation -- Conclusion: One Step at a Time.
Includes bibliographical references (p. 259-273) and index.
Keywords: Continental Organization for Global Co-operation Against Poverty in Africa; Political corruption -- Africa; Africa -- Politics and government -- 1960-; Africa -- Social conditions -- 1960-